(untitled) (Proceedings of the Global Public Health Conference, 2020)
Use of social media has become a much discussed topic in the current world. Yet there is a scarcity of research literature on the impact it makes on human lives. The impact of social media on mental health has been an important topic worldwide. Sri Lanka as a country has an ever increasing social media presence at present. While some researchers argue that there are significant negative effects of social media on mental health, current research is inconclusive on this. The current paper discusses how the use of social media creates a strong impact on the psychological condition of patients who attend psychotherapy. This impact could be both positive and negative. The paper further observes how its strong influence can be felt as precipitating, perpetuating and protective factors in the course of mental illnesses, with reference to 5 cases. The paper emphasizes the inclusion of social media impact as part of case formulation and in the design of psychotherapeutic interventions. Further it emphasizes the requirement of an individual case formulation before deciding upon whether the influence of social media on the patient is negative or positive as the impact of the social media appears to interact with individual cognitive and personality factors.